2012
DOI: 10.1007/s13239-011-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Strain and Structural Disarray Occur at the Right Ventricular Apex

Abstract: The right ventricular apex (RVA) is a potential hot spot for development of cardiac rhythm anomalies. Many conditions, including arrhythmogenic right ventricular cardiomyopathy and Brugada's syndrome affect the RVA, and further, the RVA remains an incompletely characterized pacing region. Whether there are structural reasons underlying these conduction properties remains unsettled. In the current study, we characterize the mechanical strains and structural attributes of the right ventricular wall, and test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…36 The right ventricular apex, an area preferentially affected in ARVC, exhibits heterogeneous fiber orientation and elevated incremental strains, potentially creating a mechanically weak spot in the heart. 37 Finally, electron microscopy studies of patient myocardial samples have reported decreased numbers of desmosomes and apparent clefts or widening of various components within the intercalated disks. 38 All of these observations suggest that mechanical stress plays an important role in disease progression and sudden death.…”
Section: More Than a Disease Of Abnormal Cell-cell Adhesionmentioning
confidence: 99%
“…36 The right ventricular apex, an area preferentially affected in ARVC, exhibits heterogeneous fiber orientation and elevated incremental strains, potentially creating a mechanically weak spot in the heart. 37 Finally, electron microscopy studies of patient myocardial samples have reported decreased numbers of desmosomes and apparent clefts or widening of various components within the intercalated disks. 38 All of these observations suggest that mechanical stress plays an important role in disease progression and sudden death.…”
Section: More Than a Disease Of Abnormal Cell-cell Adhesionmentioning
confidence: 99%
“…Arrhythmogenic right ventricular cardiomyopathy/dyplasia (ARVC/D) preferentially affects the right ventricular epicardium between the conus and apex, a region called “the triangle of dysplasia”. The RV wall bears higher strains for longer periods of time, has elevated changes in strain over short periods of time, and near the apex is subject to heterogeneity in strain distribution over a small volume (Hariharan et al, ). The marked disarray at the RV apex signifies abrupt changes in myocyte orientation and loss of end‐to‐end coupling.…”
Section: The Morphology Of the Right Ventriclementioning
confidence: 99%
“…20 In the splayed ‘starburst’ geometry, fibers diverge or converge, as in papillary muscle insertions in the endocardium and in the right ventricular apex, one of the corners of the ‘triangle of dysplasia’ in arrhythmogenic right ventricular cardiomyopathy. 26 In our analysis, we found that the tissue electrophysiology, in terms of AP durations and regional longitudinal and transverse conduction velocities, was similar among all of the anisotropic geometries, yielding however strikingly different and novel patterns of propagating AP waves. As discussed below, this alteration of the pattern of AP propagation, in addition to enhancing our understanding of the variability in normal organization, can be suggestive of pathological states.…”
Section: Discussionmentioning
confidence: 60%
“…It needs to be pointed out, however, that DTMRI data is 3D in nature while our current methodology is 2D, which makes translating our model of tissue patterning to this application difficult without further advancements in the technology. The precision of our method also increases the diversity of possible patterns at the cellular level, which could provide insight as to why ventricular tachyarrhythmias arise in the ventricular septum in hypertrophic cardiomyopathy 23,33 or in the right ventricular apex in arrhythmogenic right ventricular cardiomyopathy, 26 where there exist sharp direction changes and splaying of fibers. Furthermore, clinical readouts such as DTMRI imaging may be used in the future to develop personalized, computational simulations of a patient's heart and their possible risk for arrhythmias.…”
Section: Discussionmentioning
confidence: 99%